Pre-drying and submerged cap winemaking: Effects on polyphenolic compounds and sensory descriptors. Part I: BRS Rubea and BRS Cora - Machado de Castilhos, Mauricio Bonatto [UNESP]; Santos Correa, Odineli Louzada dos; Zanus, Mauro Celso; Garcia Maia, Joao Dimas; Gomez-Alonso, Sergio; Garcia-Romero, Esteban; Del Bianchi, Vanildo Luiz [UNESP]; Hermosin-Gutierrez, Isidro (Elsevier B.V., 2015)
In contrast to the most worldwide used grape varieties, wine production in Brazil is mainly devoted to the elaboration of table wines from American grapes and hybrids. These grapes show initial disadvantages such as low soluble solids content in their optimal stage of ripening and poor color quality. Based on this, the Brazilian Agency EMBRAPA Grape and Wine has developed BRS type cultivars in order to enhance the quality of the table wines. This study analyzed the phenolic composition and sensory profile of BRS Rubea and BRS Cora red wines elaborated by traditional and two alternative winemaking technologies: grape pre-drying and submerged cap of chaptalized musts. Pre-dried wines presented low concentrations of anthocyanins/pyranoanthocyanins and flavonols, suggesting that they were partially degraded by the thermal treatment (60 degrees C). These wines were described as bitter and full-bodied because of their higher flavan-3-ols content, suggesting that these compounds were not greatly influenced by thermal degradation. Submerged cap was described as persistent to the palate and with an intense violet hue due to its high anthocyanin and flavonol concentrations. The antioxidant capacity presented a weak relationship with the anthocyanins and stilbenes, but was intensely related to the % of galloylated flavan-3-ols. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Red wine; Submerged cap; Drying; Polyphenols; Sensory analysis; Antioxidant capacity